Clinical researchLeft atrial and left atrial appendage systolic function in patients with post-myocardial distal blocks - Piotrowski, Grzegorz; Szymański, Piotr; Banach, Maciej; Piotrowska, Aneta; Gawor, Rafał; Rysz, Jacek; Gawor, Zenon (Archives of Medical Science, 2010)
Introduction : The study aimed to evaluate function of the left atrium (LA) and of the left atrial appendage (LAA) after myocardial infarction (MI) complicated by intracardiac conduction disturbances. Material and methods : The study comprised 59 patients with persistent post-myocardial distal blocks, who were allocated to one of the three following subgroups: study group I – 20 patients with left bundle branch block (LBBB); study group II – 20 patients with right bundle branch block (RBBB), and study group III –19 pts with left anterior hemiblock (LAHB). The control groups included patients with MI in their history and no BBBs (19 pts – group IV) and clinically healthy people (16 patients – group V). The parameters of LA and LAA systolic function were determined by means of transthoracic (TTE) and transoesophageal echocardiography (TOE). Results : We showed that patients who experienced myocardial infarction not complicated with conduction disturbances expressed compensatory LA systolic function enhancement. In patients with post-myocardial RBBB and LAHB significant enhancement of LA systolic function was observed as well but it was expressed to a lesser degree. There was also a tendency towards deterioration of LA systolic function in patients with post-myocardial LBBB. LBBB did not affect LAA systolic function negatively. Conclusions : Parameters of LAA systolic function showed its enhancement in all patients after myocardial infarction irrespective of whether it was complicated by conduction disturbances.